Efektivitas Proses Pengadaan Produksi Melalui Metode Tender Terbatas dan Penunjukan Langsung pada PT. XYZ - Muhammad Yodha Perkasa; Sulastri Irbayuni (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This activity is a form of community service implemented through an academic partnership program with PT XYZ. The focus of the activity is on improving the effectiveness of the production procurement process through the application of best practices in Limited Tender and Direct Appointment methods. The implementation team provided guidance and technical assistance to the staff of the Production Procurement Department of the Supply Chain Division in preparing procurement documents (RKS, HPS, and bid evaluation), strengthening understanding of the principles of Good Corporate Governance (GCG), and implementing the company's internal e-procurement system. The methods used to carry out the activities included socialization, case study-based training, field observations, and evaluation of the implementation results. The results of the activities showed an increase in procurement administration capabilities, a 20% improvement in process efficiency compared to before, and increased compliance with the company's internal guidelines. This activity is a concrete example of the synergy between academia and industry in strengthening transparent, effective, and accountable procurement governance in strategic BUMN environment.